APAKAH E-WOM (ELECTRONIC WORD OF MOUTH) BISA MENGALAHKAN WOM (WORD OF MOUTH) DALAM MEMPENGARUHI PENJUALAN PRODUK KULINER - Lavenia Hariono (Kompetensi (Competence : Journal of Management Studies), 2018)
ABSTRACTGlobalization has caused a rise of so many technology developments, such as in communication. In past communication can only be used through phone call and short message. Nowadays media social became one of the communication media until promotion media which became the origin of e-WOM. WOM has been successfully becoming one of promotion strategies in the culinary business. Due to technology developments, WOM has a new model that called e-WOM especially in culinary business. Therefore, This article is expected to help marketers who are doing a critical review about e-WOM (Electronic Word of Mouth) and WOM (Word of Mouth) that became controversy in influencing culinary sales. This research method is using literature data.